Counteracting food waste as a contemporary challenge – a comparative study of Polish and German law - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2023)
The considerations presented in this article are an attempt to compare and evaluate the manner in which Poland and Germany counteract food waste. Food waste is a global problem but measures to mitigate it should be taken already at the regional and even local levels. While Poland has implemented a specific legal regulation to control food waste, there is no such specific regulation in Germany. As a matter of fact neither in Poland nor in Germany nor throughout the whole EU there exist regulations that would make it possible to counteract food waste effectively and comprehensively. Moreover, without the participation and involvement of societies, no regulations will be truly effective because the largest proportion of the waste occurs at the food consumption stage, where the possibility of the legislator’s interference is very limited. The German initiatives and experience in this field may be worth following.